Caveolin-1, GATA-3, and Ki67 expressions and their correlation with pathological findings in canine bladder urothelial carcinoma - Govoni, Verônica Mollica; Pigoli, Claudio; Brambilla, Eleonora; Ruiz Sueiro, Felipe Augusto; Torres Neto, Rafael; Laufer-Amorim, Renee; Gomes Quitzan, Juliany; Grieco, Valeria; Fonseca-Alves, Carlos Eduardo (Frontiers in Veterinary Science, 2022)
The bladder urothelial carcinoma (UC) represents about 2% of malignant neoplasms in dogs, and is a therapeutic challenge in veterinary medicine. Although it is considered the most common bladder cancer in dogs, few previous studies investigate different markers correlating with clinical and pathological parameters. Therefore, this study aimed to evaluate the Caveolin-1, GATA-3, and Ki67 immunostaining in canine UC samples, evaluating their correlations with histopathological variables. Thirty tumor samples were obtained and Caveolin-1, GATA-3 and Ki76 expression was assessed by immunohistochemistry and associated with pathological factors by univariate and multivariate analysis. Among the histopathological finding, lymphatic invasion was identified in 53.33% of the tumors, and the mean mitotic count (MC) was 31.82 ± 26.26. Caveolin-1 revealed a mild to high cytoplasmic expression in neoplastic cells, while GATA-3 showed a mild to high nuclear expression. The Ki67 expression revealed a mean of 24.14 ± 16.88% positive cells. When performed a univariate analysis, no association were found between each marker and the pathological findings. On the other hand, in multivariate analysis, we identified a positive correlation between GATA-3 and MC and a negative correlation between Caveolin-1 and MC. Moreover, lymphatic invasion was positively correlated with histological type and grade, and negatively correlated with MC. Besides that, histological type was positively correlated with histological grade. Overall, our results indicated that Caveolin-1 and GATA-3 expression could be promising markers for bladder urothelial carcinoma aggressiveness.